2009
DOI: 10.4161/cbt.8.17.9204
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by lupeol in human epidermoid carcinoma A431 cells through regulation of mitochondrial, Akt/PKB and NF-kappaB signaling pathways

Abstract: The rising incidence of skin cancer in humans makes it equivalent to malignancies of organs. Therefore, it is necessary to intensify our efforts for better understanding and development of novel treatment and preventive approaches for skin cancer. Fruits and other plant derived products have gained considerable attention as they can reduce the risk of several cancer types. Lupeol, a triterpene, present in many fruits and medicinal plants, has been shown to possess many pharmacological properties including anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Saleem et al (2008) pointed out that lupeol inhibited the growth of human metastatic melanoma cells in vitro and in vivo by up regulating Bax and caspase 3 and down regulating Bcl-2. Prasad et al (2009) reported that lupeol induced apoptosis in prostate cancer cells by up regulating Bax, caspase 3 and 9 and down regulating Bcl-2 genes. The present study are in line with other reported findings on apoptotic potential of lupeol.…”
Section: Discussionmentioning
confidence: 99%
“…Saleem et al (2008) pointed out that lupeol inhibited the growth of human metastatic melanoma cells in vitro and in vivo by up regulating Bax and caspase 3 and down regulating Bcl-2. Prasad et al (2009) reported that lupeol induced apoptosis in prostate cancer cells by up regulating Bax, caspase 3 and 9 and down regulating Bcl-2 genes. The present study are in line with other reported findings on apoptotic potential of lupeol.…”
Section: Discussionmentioning
confidence: 99%
“…Lupeol, a triterpene, is shown to possess antineoplastic effects on various human neoplastic cell lines, for example, human melanoma 451Lu cells, 18 WM35 cells, 18 and B162F2 cells 19 ; human pancreatic adenocarcinoma cells AsPC-1 20 ; human epidermoid carcinoma A431 cells 21 ; hepatocellular carcinoma SMMC7721 cells 22 ; and prostate carcinoma cell lines LNCaP, 23 CWR22Rγ1, 23 and PC-3. 24 Its cytotoxicity was selective for neoplastic cells.…”
Section: Lupeolmentioning
confidence: 99%
“…Activity-guided fractionation studies of the ethyl acetate fraction showed that the observed cytotoxic effects were primarily due to marmelin (discussed in detail in the next paragraph). 17 Additionally, experiments have also shown that the other phytochemicals such as lupeol, [18][19][20][21][22][23][24][25] eugenol, [26][27][28] citral, 29,30 cineole, 31 and d-limonene 31 present in Bael possess antineoplastic effects. In the following paragraphs, the antineoplastic effects of these phytochemicals are discussed in detail.…”
mentioning
confidence: 99%
“…For example, Lupeol was shown to suppress cisplatin induced NF-jB activation and inhibited the orthotopically implanted head and neck squamous cell carcinoma in nude mice and skin cancer in CD-1 mice [134,135]. Lupeol has been shown to inhibit several pro-inflammatory mediators and oncogenic kinases pathways such as PI3K/AKT dependent pathway [136], and pro-inflammatory molecules such as prostaglandin E2/ TNF-a/IL-1b [137]. In addition, the beneficial and pre-clinical studies using lupeol has been recently reviewed [138].…”
Section: Lupeolmentioning
confidence: 99%